Nurses' knowledge, attitudes, and behaviours related to pressure injury prevention: A large‐scale cross‐sectional survey in mainland China. Issue 17 (14th July 2020) - Jiang, Ling; Li, Li; Lommel, Lisa
Abstract: Aims and objectives: To determine the level of and factors in nurses' knowledge, attitudes and behaviours towards pressure injury (PI) prevention. Background: Although there has been a declining trend in global PI prevalence and hospital‐acquired rates in recent years, this has not been the case in China. Evidence in the literature indicates the importance of nurses' knowledge, attitudes and behaviours for promoting PI prevention. Design: Cross‐sectional study. Methods: A total of 1, 806 nurses from 10 tertiary general hospitals in Hunan Province, China, participated in this study. Nurses' knowledge and attitudes were assessed using Pieper's Pressure Ulcer Knowledge Test and Attitude towards Pressure Ulcer Prevention Instrument, respectively, and behaviours were measured using a researcher self‐designed questionnaire. Multiple logistic regression analysis determined factors affecting the nurses' PI‐prevention knowledge, attitudes and behaviours. A STROBE checklist was used to report findings. Results: Among all nurses involved in this study, 41.7% had insufficient PI‐prevention knowledge, 46.6% had negative PI‐prevention attitudes, and 21.8% had poor PI‐prevention behaviour. Nurses with a bachelor's degree or above were more likely to have adequate PI‐prevention knowledge. Increased PI‐prevention training frequency increased the nurses' positive attitude scores for PI prevention; longer years of service and a higher number of PI‐prevention trainings attended predicted better PI‐prevention behaviours. Conclusion: Chinese nurses' PI‐prevention knowledge and attitudes in this study were unsatisfactory, while their PI‐prevention behaviour was acceptable. Increasing PI‐prevention training frequency can help improve Chinese nurses' PI‐prevention attitudes and further behaviour. Having a minimum of a bachelor degree may be beneficial to Chinese nurses' PI‐prevention knowledge, but more evidence is needed. Relevance to clinical practice: Chinese nurses have insufficient knowledge about PI‐repositioning, inadequate practices in PI nutrition assessment, and low confidence in their personal competence regarding PI‐prevention. The key solution for the above issues is to promote ongoing education and training based on strong clinical leadership.